European stakeholder perspectives on challenges to rare disease drug development – a qualitative study. (3rd June 2021) - Joshi, Sarala; Chen, Jessica; Sultan, Mustafa; Singh, Shefali; Abedi, Syed; Zheng, Sifan
ABSTRACT: Background: The multifaceted challenges of rare disease research remain, leaving a large proportion of rare disease patients without treatment options. This study aims to identify the challenges of rare disease drug development. Research design & methods: Ten semi-structured interviews were carried out with a range of stakeholders. Thematic analysis was conducted to identify common and important themes. Results: Four overarching themes of stakeholder engagement, regulatory structure, data, and patient support were identified, encompassing fifteen subthemes. Conclusion: The presence of an active patient group is a significant factor in reducing barriers to rare diseases treatment development. Effective collaboration between the various stakeholders of rare disease research is crucial.